Nebivolol and quinapril reduce P-wave duration and dispersion in hypertensive patients - Korkmaz, Hasan; Onalan, Orhan; Akbulut, Mehmet; Ozbay, Yilmaz (My University, 2009)
We aimed to investigate the effects of nebivolol and quinapril treatments on P-wave duration and dispersion in hypertensive patients. Hypertensive patients who were in sinus rhythm were assigned to the two treatment groups and received either 20 mg quinapril/day or 5 mg nebivolol/day. P-Wave dispersion (PWD) was measured at baseline and after four weeks of treatment and defined as the difference between the maximum (Pmax) and the minimum (Pmin) P-wave duration. The study group consisted of 54 patients (Mean age: 53 ± 9 years, 46% women) with 27 patients in each group. At 4-week follow up both treatment groups showed a significant reduction (p<0.001) in systolic (SBP) and diastolic blood pressure (DBP). Heart rate (HR) reduction was significant in patients receiving nebivolol (P=0.001). Both groups showed a similar (P=0.413 for PWD, p=0.651 for Pmax) but significant reduction in PWD (nebivolol: -16±14, P<0.0001 and quinapril: -13±11, P<0.0001) and Pmax (nebivolol: -10±11, P=0.001 and quinapril: -9±11, P=0.001). A 2 (Time) × 2 (Group) mixed-model repeated-measures analysis of variance revealed that the main effect of Time was significant for Pmax (P=0.002) and PWD (P=0.008) after controlling for changes in SBP, DBP and HR. However, the main effect of Group and Time x Group interaction was not significant for both variables (All p values >0.05). In conclusion, short-term treatment with nebivolol and quinapril produces a similar but significant reduction in Pmax and PWD in hypertensive patients. This effect is independent of blood pressure and heart rate changes.
Keywords: Hypertension; Nebivolol; P-wave duration; Quinapril